1990
DOI: 10.1083/jcb.110.4.1103
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate-induced calcium release in the organelle layers of the stratified, intact egg of Xenopus laevis.

Abstract: Abstract. Using double-barreled, Ca2÷-sensitive microelectrodes, we have examined the characteristics of the Ca 2+ release by inositol 1,4,5-trisphosphate (Ins(1,4,5)P3) in the various layers of Xenopus laevis eggs in which the organelles had been stratified by centrifugation. Centrifugation of living eggs stratifies the organelles yet retains them in the normal cytoplasmic milieu. The local increase in intracellular free Ca 2+ in each layer was directly measured under physiological conditions using theta-tubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Fig. 3A shows a photomicrograph of the centrifuged oocytes, in which [Ca 2ϩ ] i increases in response to IP 3 and thapsigargin were previously localized to the portion of the oocyte enriched for the ER (17,30). Our observations also showed maximal [Ca 2ϩ ] i increases near this band and were faithfully mimicked by a model based on a diffusible CIF produced only by the ER-enriched band (A.B., P.C., R.B.M., and J.E.K., manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 3A shows a photomicrograph of the centrifuged oocytes, in which [Ca 2ϩ ] i increases in response to IP 3 and thapsigargin were previously localized to the portion of the oocyte enriched for the ER (17,30). Our observations also showed maximal [Ca 2ϩ ] i increases near this band and were faithfully mimicked by a model based on a diffusible CIF produced only by the ER-enriched band (A.B., P.C., R.B.M., and J.E.K., manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…After 30 min, the oocytes in some experiments were transferred to a centrifuge tube containing 5 ml 30% Ficoll 400. Stratification was carried out at 4,000 ϫ g for 1 hr (17). The oocytes were oriented on the microscope stage with the animal pole facing the objective or, for those that were centrifuged, so that all four layers of the stratified oocyte were visible in the optical plane.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to changes that occur in the nucleus during GVBD, oocyte maturation can also trigger marked alterations in cytoplasmic organelles. For example, the endoplasmic reticulum (ER), which most probably represents the major internal store of Ca 2+ to be mobilized at fertilization (Eisen and Reynolds, 1985;Han and Nuccitelli, 1990;Terasaki and Sardet, 1991), develops discrete aggregates (i.e. 'clusters' or 'microdomains') in the maturing oocytes of several animal groups that have been investigated (Kline, 2000;Sardet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is noteworthy that recent studies on IP3-induced Ca2+ release in stratified eggs of Xenopus laevis have demonstrated that although all organelle layers are able to release (and sequester) Ca2+, the reticulum-enriched layer releases ten fold as much Ca2+ (17).…”
Section: Discussionmentioning
confidence: 99%